The Status and Job Satisfaction of Computer Operators - Gluck, Adrian; Evans, Martin (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1972)
The results of this exploratory study suggest that computer operators experience a high level of inconsistency in their occupational status. Such inconsistency produces a differential impact upon the satisfaction of computer operators. When operators resolve the inconsistency by seeing their own status as low, they tend to be dissatisfied ; when they see their own status as high, they tend to be satisfied.